(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Omega3 is a group of fatty acids which is essential and of great importance to the human body, they cannot be produced on their own, so it must be obtained by following diets that include foods rich in them. Omega 3 is nowadays one of the most desirable components of oils because of its nutritional and functional properties. Through its various processes in cellular metabolism, its therapeutic actions in numerous chronic inflammatory and autoimmune disorders have been identified, gene expression, and signal transduction. Numerous studies have confirmed that acne, psoriasis, and inflammatory skin conditions including atopic dermatitis can all be managed with omega 3. Objective: The review’s objective is to provide a brief scientific overview of this condition, which has recently become widespread used in the treatment of skin diseases. Conclusion: The effects of "3 PUFA" in skin illnesses are only seldom studied in research and clinical trials, but prior studies analyzing immune cells predict that these fatty acids will have a wide range of positive benefits. Additionally, there are few findings on keratinocytes, which are thought to make up a significant portion of the epidermis’ cells. Future studies should clarify the complete role keratinocytes play in the skin. since the prevalence of inflammatory skin conditions and cancers is rising at the moment, clinical trials in the future on "3 PUFAs" in dermatological sectors are likely to provide us with useful knowledge for the routine clinical management of skin problems. Keywords: Polyunsaturated fatty acids, "PUFAs," omega-3, psoriasis, skin.